Regulation of aortic CuZn-superoxide dismutase with copper. Caeruloplasmin and albumin re-activate and transfer copper to the enzyme in culture. - Dameron, C T (1987)
Caeruloplasmin and albumin were compared as potential donors of copper to Cu2Zn2-superoxide dismutase (CuZn-SOD) in culture. Aortas from 15-day copper-deficient chicks were suspended in oxygenated, serum-free, Waymouth medium (752/1) for 24 h. SOD activity was restored when the medium was supplemented with CuCl2, a copper-albumin complex or caeruloplasmin, all present at a level equivalent to 5 microM-copper. Activation did not occur at 4 degrees C or with Cu-EDTA as the supplement. Mn2+ and Zn2+, alone or in combination, did not activate nor enhance the activation achieved by CuCl2. The activation with CuCl2 was not inhibited by cycloheximide or cordycepin. [67Cu]Caeruloplasmin and albumin when added to the medium transferred radioactive copper to at least three cytosolic protein fractions, one of which was determined by immunoprecipitation to be CuZn-SOD. The transfer of 67Cu from caeruloplasmin was inhibited by increasing amounts of unlabelled caeruloplasmin; disodium EDTA (1.0 mM) had no effect on the transfer of copper from caeruloplasmin. These data show that aortic SOD activity, suppressed in copper deficiency, can be restored by incubating the aortas in culture medium supplemented with copper salts. In this system, caeruloplasmin and Cu-albumin appear equally capable of activating aortic CuZn-SOD. Moreover, the transfer of copper into the enzyme structure appears to be the primary event restoring catalytic activity to the enzyme.